Internal quality assurance in a clinical virology laboratory. I. Internal quality assessment. Issue 2 (February 1995) - Gray, J J; Wreghitt, T G; McKee, T A; McIntyre, P; Roth, C E; Smith, D J; Sutehall, G; Higgins, G; Geraghty, R; Whetstone, R
Abstract : AIMS–In April 1991 an internal quality assessment scheme (IQAS) was introduced into the virology section of the Clinical Microbiology and Public Health Laboratory, Cambridge. The IQAS was established to identify recurring technical and procedural problems, to check the adequacy of current techniques, and to calculate the frequency of errors. METHODS–Between April 1991 and December 1993, 715 anonymous clinical serum samples were submitted to the laboratory to test 3245 individual procedures of diagnostic viral serology. RESULTS–A total of 485 (14.9%) procedural and 61 (1.9%) technical discrepancies were observed, the technical discrepancies mainly being recorded in complement fixation tests. Twenty two (0.7% of total procedures) of the technical discrepancies were diagnostically significant. CONCLUSIONS–Evaluation criteria developed with the introduction of IQAS to viral serology, and technical and procedural discrepancies are assessed. As yet, IQAS has not been introduced to other sections of the diagnostic virology laboratory (virus isolation, electron microscopy, immunofluorescence, and enzyme linked immunosorbent assays for viral and chlamydial antigens).